2014
DOI: 10.1111/iej.12402
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the full‐scale Periapical Index

Abstract: Repeated radiographic assessments of teeth using the full-scale PAI reveal that each of the five scores had distinct prognostic value for the course of periapical disease over a 5-year period for both nonroot filled and root filled teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 13 publications
(16 reference statements)
0
39
0
10
Order By: Relevance
“…Of these registrations, 46 were not included in the analyses due to insufficient quality of one or both radiographs (Kirkevang et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Of these registrations, 46 were not included in the analyses due to insufficient quality of one or both radiographs (Kirkevang et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…, Kirkevang et al . ). In a recent Danish study, it was demonstrated that each of the five PAI scores had a specific predictive value in relation to the future periapical status both regarding non‐root filled and root filled teeth (Kirkevang et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Zróżnicowane obserwacje dotyczące tego zagadnienia wyjaśniają w pewnym stopniu badania Kirkevang et al, 30 którzy zbadali grupę szwedzkich pacjentów pod kątem identyfikacji czynników ryzyka utraty zębów. Autorzy podczas dziesięcioletniej obserwacji zębów ze zdia gnozowanym na początku badania zapaleniem przyzę bia wierzchołkowego zauważyli, że część z nich została w tym czasie usunięta, nie podlegając tym samym dal szej ocenie.…”
Section: Omówienieunclassified
“…The success of the endodontic treatment can be affected by four factors in a positive or negative way: 1) the presence or absence of apical periodontitis, 2) the apical density, 3) apical extension of the radicular obturation, and 4) the quality of the final restoration. It has been observed that teeth with previous endodontic treatment without a final restoration or with poorly adjusted treatment shows the worst periapical healing (Haapasalo et al, 2011;Liang et al, 2011;Kirkevang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%